EVALUATION OF DISCHARGE READINESS IN A PATIENT WITH SECONDARY STROKE: A CASE STUDY - Kadir, Afrizal Nur; Septianingrum, Yurike; Wijayanti, Lono (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Early readmission in stroke survivors remains a critical issue, particularly in patients with mild initial symptoms but who experience early recurrence within a short period. Evaluating both patient and caregiver readiness for discharge is essential to improve home care outcomes and prevent avoidable hospitalizations. Objectives: This case study aims to assess discharge readiness in a post-stroke patient and their caregiver using the PATH-s instrument and examine its implications for readmission prevention. Methods: A descriptive single-case study was conducted involving a 66-year-old male with a secondary ischemic stroke within 30 days of the initial attack. Data were collected via clinical records and interviews. Discharge readiness was evaluated using the Preparedness Assessment for the Transition Home after Stroke (PATH-s) instrument, consisting of 25 items. The assessment was guided through a structured interview due to the patient's limited ability to self-complete the questionnaire. Results: The PATH-s assessment yielded a total score of 69 out of 100, indicating a moderate level of discharge readiness. The average score per item was 2.67 out of 4, suggesting a need for additional support in specific areas. The domains identified for improvement included financial capacity, home and transportation accessibility, long-term prognosis, and patient insight about stroke. Conclusion: Evaluating discharge readiness in the patient and family caregiver helped increase awareness of home care limitations and guided appropriate nursing interventions. These findings highlight the value of structured assessments like PATH-s in supporting clinical decision-making and individualized discharge planning.